2019
DOI: 10.12691/jfnr-7-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Modified Atmosphere Package and Short-Wave Ultraviolet Does Not Affect <i>Proteus </i><i>m</i><i>irabilis</i> Growth on Rainbow Trout Fillets (<i>Oncorhynchus m</i><i>ykiss</i>)

Abstract: The current study investigated the effectiveness of short-wave ultraviolet (UV-C) radiation on rainbow trout fillets inoculated with Proteus mirabilis when combined with Modified Atmosphere Packaging technology (MAP). Rainbow trout were inoculated, packaged under different ratios of CO 2 and N 2 gases and subjected to UV-C radiation. Our study model demonstrated that at least 0.1001 J/cm 2 is necessary to significantly reduce Proteus mirabilis loads (reduction of 1.8 log CFU.g -1 ) in trout fillet packaged wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…MAP/UV was ineffective against the growth of both evaluated pathogens, and it was better observed for Escherichia coli O157:H7. These findings may be explained because MAP can impair the penetration power of the UV-C radiation at 0.30 J/cm 2 as well as to the higher ability of adaptation of E. coli compared to S. enterica [ 20 , 39 , 40 ]. Rodrigues et al [ 20 ] observed that MAP (50% CO 2 /50% N 2 ) was a barrier to penetration of UV-C radiation in rainbow trout fillets.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…MAP/UV was ineffective against the growth of both evaluated pathogens, and it was better observed for Escherichia coli O157:H7. These findings may be explained because MAP can impair the penetration power of the UV-C radiation at 0.30 J/cm 2 as well as to the higher ability of adaptation of E. coli compared to S. enterica [ 20 , 39 , 40 ]. Rodrigues et al [ 20 ] observed that MAP (50% CO 2 /50% N 2 ) was a barrier to penetration of UV-C radiation in rainbow trout fillets.…”
Section: Resultsmentioning
confidence: 99%
“…and E. coli in meat. However, Rodrigues et al [ 20 ] reported that combined MAP (30% CO 2 /70% N 2, 50% CO 2 /50% N 2 , and 70% CO 2 /30% N 2 ) and UV-C radiation (0.04, 0.06, and 0.10 J/cm 2 ) were ineffective on the reduction of Proteus mirabilis in rainbow trout fillets. It is worth highlighting that Proteus mirabilis is a Gram-negative and facultative anaerobic bacteria, as well as S. typhimurium and E. coli O157:H7 [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations